Analisis Spasial Faktor Resiko Sebaran Penyakit Tuberkulosis Di UPTD Puskesmas Medan Satria - Al Faqih, M. Rolan Tiro; Dewi, Deasy Rosmala; Widjaja, Liliy; Yulia, Noor (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the spatial distribution patterns of Tuberculosis (TB) cases and identify the contributing risk factors in the working area of UPTD Medan Satria Health Center. TB remains a serious public health problem in Indonesia due to its high transmission rate and increasing number of cases. The study employed a descriptive quantitative method with a cross-sectional approach, involving 55 TB patients recorded throughout 2024. Data were collected through field observation, documentation from the SIMPUS information system, and analyzed using QGIS software to produce spatial maps. The findings revealed that RW 009 had the highest number of TB cases. This area also had very high population density and limited access to healthcare facilities. Population density and limited access to health services were found to influence TB distribution, while smoking behavior did not show a significant relationship. Therefore, spatial analysis proves useful in identifying priority intervention areas and designing more effective and targeted TB prevention and control strategies in the community.